Auction Procedure for Dependent Rights as an Effort to Resolve Non-Litigation of Non-Performing Loans by Banks - Taufiq, Taufiq; Napitupulu, Diana Ria Winanti (Faculty of Law, Universitas Pattimura, 2025)
Introduction: Non-performing loans are a major challenge in banking operations that can affect the financial stability and operational performance of banks. One of the non-litigation solutions pursued by banks to resolve such issues is through the auction of mortgage rights over the debtor's collateral.Purposes of the Research: This study aims to examine in detail the procedure for conducting mortgage right auctions as a means of resolving non-performing loans and to assess their effectiveness in providing legal protection for banks.Methods of the Research: The research method used is normative juridical with a statutory and case study approach. Normative Juridical Approach is chosen because the main focus of the research is to analyze and examine the applicable legal norms related to the procedure of mortgage right auctions as a solution for resolving non-performing loans.Findings of the Research: The results show that the auction of mortgage rights is carried out through the State Assets and Auction Service Office (KPKNL) based on Law Number 4 of 1996 on Mortgage Rights and relevant Minister of Finance Regulations. The procedure includes stages such as notification, collateral assessment, auction announcement, auction execution, and distribution of auction proceeds. Although this process offers a more efficient alternative compared to litigation, practical obstacles still exist, such as debtor objections, lengthy auction processes, and administrative hurdles. Therefore, regulatory harmonization and improved coordination between banks, KPKNL, and relevant parties are necessary to enhance the effectiveness of mortgage right auctions as a non-litigation solution for non-performing loans.